Evaluation of Nausea and Vomiting Severity in Pregnancies Conceived Through Assisted Reproduction - Yucel Cicek, Ozge Senem; Demir, Merve (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: This study aimed to evaluate the severity of nausea vomiting of pregnancy in assisted reproductive technologies pregnancies using the Pregnancy-Unique Quantification of Emesis scoring system which is a validated, clinically relevant method to assess nausea vomiting of pregnancy severity. STUDY DESİGN: A total of 101 pregnant women between 8+0-14+6 weeks of gestation were enrolled in this case-control study. Of these women, 53 had pregnancies conceived via assisted reproductive technologies (study group) and 48 had pregnancies conceived naturally (control group). The Pregnancy-Unique Quantification of Emesis-24 scale was utilized to evaluate nausea vomiting of pregnancy severity in both groups. Weight change during pregnancy and hospital admission due to nausea vomiting of pregnancy were also compared to assess severe nausea vomiting of pregnancy. RESULTS: According to the Pregnancy-Unique Quantification of Emesis scale, 67.9% of patients with assisted reproductive technologies pregnancies experienced mild nausea vomiting of pregnancy while 24.5% had moderate and 7.5% had severe nausea vomiting of pregnancy. In the spontaneous pregnancies group, 60.4% experienced mild nausea vomiting of pregnancy, 33.3% had moderate nausea vomiting of pregnancy and only 6.3% had severe nausea vomiting of pregnancy. The overall Pregnancy-Unique Quantification of Emesis score was 5 (3-8.5) in assisted reproductive technologies pregnancies and 5 (3-10) in spontaneous pregnancies (p=0.650). There was no statistically significant difference regarding hospitalization history due to nausea vomiting of pregnancy between assisted reproductive technologies and naturally-conceived pregnancies (p=0.619). CONCLUSION: Conception using assisted reproductive technologies does not increase nausea vomiting of pregnancy severity. Furthermore, weight change during pregnancy and hospitalization rates due to nausea vomiting of pregnancy were comparable between women conceived with assisted reproductive technologies and women with natural conception.